2001
DOI: 10.1007/s001250100547
|View full text |Cite
|
Sign up to set email alerts
|

Diet and risk of Type II diabetes: the role of types of fat and carbohydrate

Abstract: The prevalence of Type II (non-insulin-dependent) diabetes mellitus is increasing rapidly in the United States [1] and worldwide [2]. Prevalence of diabetes in adults in the world is estimated to reach 5.4 % and the number of adults with diabetes to reach 300 million worldwide in the year 2025 [2]. The toll of diabetes on health and the economy is enormous and will continue to rise. Because there is no currently available cure for diabetes, primary prevention through diet and lifestyle modification is of param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
409
4
15

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(443 citation statements)
references
References 76 publications
15
409
4
15
Order By: Relevance
“…Type of fat (namely, high saturated and trans-fatty acid and low unsaturated fatty acid intake), rather than total fat intake, has in several studies been associated with increased diabetes risk [48]. In our study the total and saturated fat intakes were highly correlated (r=0.81) and the intake of mono-unsaturated fat remained relatively stable throughout the study.…”
Section: Discussionsupporting
confidence: 55%
“…Type of fat (namely, high saturated and trans-fatty acid and low unsaturated fatty acid intake), rather than total fat intake, has in several studies been associated with increased diabetes risk [48]. In our study the total and saturated fat intakes were highly correlated (r=0.81) and the intake of mono-unsaturated fat remained relatively stable throughout the study.…”
Section: Discussionsupporting
confidence: 55%
“…Although the controversy in earlier data concerning marine fatty acids and glucose metabolism (Salomaa et al, 1990;Feskens et al, 1991Feskens et al, , 1995Borkman et al, 1993;Adler et al, 1994;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Baur et al, 1998;Gustafsson et al, 1998;Bjerregaard et al, 2000;Ekblond et al, 2000;Mori et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004;Thorsdottir et al, 2004) may be partly explained by different doses and durations of supplementation in intervention studies, and by different background diets between the study populations, inclusion of subjects with different PPARG Pro12Ala genotypes could also influence the outcome of the study. That PPARG genotype may affect the associations of dietary fat composition with insulin concentrations (Luan et al, 2001) and serum triacylglycerol response to fish oil supplementation (Lindi et al, 2003) was suggested previously.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, long-chain nÀ3 polyunsaturated fatty acids have been found to be associated with enhanced glucose metabolism (Feskens et al, 1991;Adler et al, 1994;Feskens et al, 1995;Baur et al, 1998;Ekblond et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Thorsdottir et al, 2004) and to lower serum free fatty acid (FFA) concentrations (Gustafsson et al, 1998), although there are also contradictory results (Salomaa et al, 1990;Borkman et al, 1993;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Bjerregaard et al, 2000;Mori et al, 2000;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004). It is not known whether some of the discrepancies in previous results could be attributed to differences in the genetic background of the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…High fat intake may contribute to the development of diabetes via obesity. Findings of several studies suggest that higher intake of polyunsaturated fat and possibly long-chain n-3 fatty acids could be beneficial in prevention of type II diabetes, whereas higher intake of saturated fat and trans-fat may be detrimental (Hu et al, 2001b). Other dietary factors that have been related to reduced risk of type II diabetes include coffee (van Dam & Feskens, 2002;Tuomilehto et al, 2004), dairy products , and vitamin D (Baynes et al, 1997).…”
Section: Introductionmentioning
confidence: 99%